Case report: Interstitial pneumonitis after initiation of lamotrigine - Watzal, Victoria; Godbersen, Godber Mathis; Weidenauer, Ana; Willeit, Matthäus; Popper, Valentin; Treiber, Michael; Preiss, Maximilian; Ivkic, Dominik; Rabl, Ulrich; Fugger, Gernot; Frey, Richard; Kraus, Christoph; et al. (Frontiers in Psychiatry, 2023)
The second-generation anticonvulsant lamotrigine is widely used in the psychiatric field as a mood stabilizer or antidepressant augmentation therapy. Although particularly older anticonvulsants are known for their potential to cause hypersensitivity syndromes, newer antiepileptic drugs do hold a certain risk as well. Presenting a case of a 32-year-old male inpatient of African ethnicity suffering from a primary severe depressive episode in the course of a recurrent major depressive disorder, we report the occurrence of a rapid-onset drug-induced pneumonitis. Herewith, the interstitial pneumonitis occurred after the initiation of 25 mg lamotrigine as an augmentation therapy. Except for the clear temporal correlation between the administration of lamotrigine and the onset of pneumonitis, we did not reveal any further potentially causal diagnostic hints. Importantly, no relevant genetic variations of metabolizing enzymes or drug interactions resulting in lamotrigine overdosage as a potential cause of toxicity were identified. Our experience with a potentially life-threatening adverse drug reaction shortly after the initiation of the largely well-tolerated lamotrigine suggests a potential side effect under the second-generation anticonvulsant although similar adverse events are deemed to be very rare.